Nursing and health policy perspectives 2020 – a year to remember or one to forget?. (11th January 2021) - Catton, Howard
Abstract : 2020 has certainly been a year of challenges for nurses and healthcare workers around the world with the relentless spread of COVID‐19. These challenges are many, including countries and health systems not being prepared for a pandemic, shortages of personal protective equipment and acute shortages of nurses, poor communication from governments and the lack of accurate data regarding COVID‐19 morbidity and mortality among nurses and health workers. Nurses are suffering from psychological distress and are exhausted and burntout as the pandemic's second wave moves around the world. Many have been subjected to violence and aggression from people in their communities. Against this backdrop, nurses' contributions have been vital in saving lives and the profession has learnt many powerful lessons that will resonate in nursing practice for the future. But governments must do more, including ensuring nurses receive vaccinations early to protect them when a successful vaccine becomes available.